A Highly Selective Fluorescent Probe for Hypochlorous Acid in Living Cells Based on a Naphthalene Derivative. (14th February 2022) - Sun, Jingguo; Xu, Junhong; Ma, Qiujuan; Mao, Guojiang; Zhu, Nannan; Tian, Meiju; Li, Linke; Liu, Shuzhen
Abstract : Hypochlorous acid (HOCl) was crucial for maintaining the homeostasis in cells and plays vital roles in many physiological and pathological processes. In this work, a highly selective fluorescent probe for hypochlorous acid in living cells was constructed and prepared based on a naphthalene derivative. A naphthalene derivative was utilized as the fluorescent group, and N, N -dimethylthiocarbamate was applied as the selective recognition site for HOCl. Before adding HOCl, the fluorescent probe exhibited weak fluorescence. Upon adding HOCl, the fluorescent probe displayed remarkable fluorescence enhancement. The fluorescence intensity at 502 nm showed a linear response to the concentration of HOCl from 3.0 × 10 −7 to 1.0 × 10 −5 mol·L −1 . The detection limit was estimated to be 1.5 × 10 −7 mol·L −1 for HOCl. The fluorescent probe showed fast response and outstanding selectivity toward HOCl. It owned good biocompatibility and had also been successfully applied in the confocal imaging of exogenous and endogenous HOCl in living cells.